Current Challenges Arising during Pandemic COVID-19: A Mini Review - Fahmida Khatoon; Amal Daher Alshammari (New Horizons in Medicine and Medical Research Vol. 8, 2022)
In the end of 2019 severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; which also known as 2019 novel coronavirus or 2019-nCoV) disease (COVID-19) outbreak occur in China represent one of the most chief health problems. World health organization in February shown that about 43 000 well confirmed cases have been diagnosed in number of countries and regions all over the world, most of them was in China. WHO stated that COVID- 19 as sixth public heath disaster of global concern on the end of January 2020COVID- 19 outbreak happen regarding as one of most aggressive pandemic occur in near close decades with uncommon viral pneumonia started in Whuhan , China and then globally. During Pandemic many challenges face by every country and education lies the most and one of the biggest challenge during these days. Challenges arising from the COVID pandemic arise around: Psychological Teaching and Learning Health and wellbeing Assessment and Progression of students Social Economic Transportation ,Mobility, Travel, accommodation, campus safety